David Bergelson's strange new world : untimeliness and futurity - Murav, Harriet, 1955- (Jews in Eastern Europe (Bloomington, Ind.), 2019)
David Bergelson's Strange New World explores the work of one of the most highly regarded Yiddish writers of the 20th and his untimely world of characters who live ahead and behind the times in the Eastern European shtetl.